Impact of extracellular vesicles on the pathogenesis, diagnosis, and potential therapy in cardiopulmonary disease - Soto-Vázquez, Yixel M.; Genschmer, Kristopher R. (Frontiers in Pharmacology, 2023)
Cardiopulmonary diseases span a wide breadth of conditions affecting both heart and lung, the burden of which is globally significant. Chronic pulmonary disease and cardiovascular disease are two of the leading causes of morbidity and mortality worldwide. This makes it critical to understand disease pathogenesis, thereby providing new diagnostic and therapeutic avenues to improve clinical outcomes. Extracellular vesicles provide insight into all three of these features of the disease. Extracellular vesicles are membrane-bound vesicles released by a multitude, if not all, cell types and are involved in multiple physiological and pathological processes that play an important role in intercellular communication. They can be isolated from bodily fluids, such as blood, urine, and saliva, and their contents include a variety of proteins, proteases, and microRNA. These vesicles have shown to act as effective transmitters of biological signals within the heart and lung and have roles in the pathogenesis and diagnosis of multiple cardiopulmonary diseases as well as demonstrate potential as therapeutic agents to treat said conditions. In this review article, we will discuss the role these extracellular vesicles play in the diagnosis, pathogenesis, and therapeutic possibilities of cardiovascular, pulmonary, and infection-related cardiopulmonary diseases.